Patterns of Code-Switching in English Speaking Practice: A Descriptive Analysis of University Students - Syava Aizhawa Putri Nurina; Aminah Suriaman; Fadhilah Zamzam; Mochtar Marhum (MASI Mandiri Edukasi, 2026)
Many university students experience difficulties in academic English speaking due to limited vocabulary, grammatical problems, nervousness, and the need to convey ideas clearly. To cope with these challenges, students often switch between English and Bahasa Indonesia during speaking activities. This study aims to examine the frequency of code-switching in academic speaking and to identify the main factors influencing its use among EFL university students. This study employed a quantitative descriptive design involving 32 third-semester students in an English for Public Speaking course at Tadulako University. Data were collected through a 20-item questionnaire covering linguistic, psychological, communicative, and social factors, supported by semi-structured interviews. Descriptive statistics were used to analyze the data. The findings reveal that code-switching occurs very frequently, with 96.88% of students reporting frequent use. Linguistic factors were the most dominant, followed by social and communicative factors, while psychological factors had the lowest influence. Interview data confirmed that students use code-switching to maintain fluency, clarify meaning, and support interaction. Overall, code-switching is a common and strategic practice that helps students manage academic speaking challenges in multilingual EFL classrooms.